La autoestima de las trabajadoras sexuales y el efecto en su entorno familiar en la Parroquia San Carlos del Cantón Quevedo en el año 2014 - Suarez Chiquito, Jessenia Maribel (2014)
Prostitution is an economic activity that make their living thousands of people, mostly women, worldwide. Approaching the subject regardless of their views without having clear, what are the alternative job possibilities, far from helping them generate problems. Trying to "save" people without their consent can be a well-intentioned position, but is not an effective way to address the situation. It is also necessary to know their emotional state and the effects on their homes and the conditions under which they operate. Also, the trigger effects on your family. For the development of this research collection of scientific material from texts, journals and scientific papers, as well as surveys and interviews with those involved in the investigation, it was determined that using the descriptive analytical, to be considered one population between citizenship and sex workers in the city of Quevedo, showing that not all sex workers feel good about their work, most have problems to socialize and also face discrimination